PHB Biosynthesis Counteracts Redox Stress in Herbaspirillum seropedicae - Batista, Marcelo B.; Teixeira, Cícero S.; Sfeir, Michelle Z. T.; Alves, Luis P. S.; Valdameri, Glaucio; Pedrosa, Fabio de Oliveira; Sassaki, Guilherme L.; Steffens, Maria B. R.; de Souza, Emanuel M.; Dixon, Ray; Müller-Santos, Marcelo (Frontiers in Microbiology, 2018)
The ability of bacteria to produce polyhydroxyalkanoates such as PHB enables provision of a carbon storage molecule that can be mobilised under demanding physiological conditions. However, the precise function of PHB in cellular metabolism has not been clearly defined. In order to determine the impact of PHB production on global physiology, we have characterised the properties of a ΔphaC1 mutant strain of the diazotrophic bacterium Herbaspirillum seropedicae. The absence of PHB in the mutant strain not only perturbs redox balance and increases oxidative stress, but also influences the activity of the redox-sensing Fnr transcription regulators, resulting in significant changes in expression of the cytochrome c-branch of the electron transport chain. The synthesis of PHB is itself dependent on the Fnr1 and Fnr3 proteins resulting in a cyclic dependency that couples synthesis of PHB with redox regulation. Transcriptional profiling of the ΔphaC1 mutant reveals that the loss of PHB synthesis affects the expression of many genes, including approximately 30% of the Fnr regulon.